Communal Dining in the Roman West : Private Munificence Towards Cities and Associations in the First Three Centuries AD - Wen, Shanshan, (Mnemosyne, Supplements ;, 2022)
Communal Dining in in the Roman West explores why the practice of privately sponsored communal dining gained popularity in certain parts of the Western Roman Empire for almost 300 years. This book brings together 350 Latin inscriptions to examine the benefactors and beneficiaries, the geographical and chronological distributions, and the relationship between public and collegial dining practices. It argues that food-related euergetism was a region-specific phenomenon which was rooted in specific social and political cultures in the communities of Italy, Baetica and Africa Proconsularis. The region-specific differences in political cultures and long-term changes in these cultures are key to understanding not only the long persistence of this practice but also its ultimate disappearance.